ДВОХОБМОТКОВИЙ БЕЗЗАЛІЗНИЙ ІНДУКТОР БІЖУЧОГО МАГНІТНОГО ПОЛЯ - Карлов, О.М.; Кондратенко, І.П.; Крищук, Р.С.; Ращепкін, А.П. (Інститут електродинаміки Національної академії наук України, 2018)
Here, the use of non-iron three-phase high-frequency magnetic field inductors is proposed. It make it possible to eliminate noise in production and eliminate one-sided attraction in the temperature treatment of ferromagnetic strips. The use of two-winding inductors with different pole division and with a regulated value of the voltage of the windings is proposed for the purpose of controlling the uniformity of heating. The identical design of the upper and lower two-winding inductors is proposed for stabilizing the position of the band along the center of the gap. This is achieved by placing both windings in the slots of each inductor. Both equally directed and reverse directed rotational fields can be excited by switching the phase supply by the phase currents of each winding. If it is necessary to compensate the large longitudinal tension of the strip, this is used. Methods for calculating the apparent complex power of both windings are developed using the system of Maxwell equations. The normal and tangential forces acting on the ferromagnetic strip at its arbitrary asymmetric position in the gap are determined. The frequency of the current ensures the stabilization of the strip along the axis of the gap. It was investigated here that the choice of frequency depends on the geometric dimensions and electrophysical properties of the strip. The method for calculating the distribution of heat and the distribution of the temperature field along the length and width of a moving strip is developed. The use of a two-winding inductor to ensure uniform heating of the strip of various sizes is shown. References 11, figures 7.